Improving Student Learning Outcomes Using Quizizz Interactive Quizzes at SMK Negeri 4 Gowa - Saskia; Abdul Muis Mappalotteng; Andi Sitti Rasiah (Journal of Education for Creativity and Innovation, 2026)
The development of digital technology has encouraged the need for innovation in the learning process to improve students’ learning outcomes and engagement. One form of such innovation is the use of technology-based interactive quizzes such as Quizizz. This study aims to improve the learning outcomes of Grade X students at SMK Negeri 4 Gowa through the implementation of Quizizz as an interactive learning medium. The research employed Classroom Action Research conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The research subjects were 30 Grade X students. Data were collected through learning outcome tests, observations of student activities, and questionnaires on students’ responses to the use of Quizizz. The results showed a significant improvement in students’ learning outcomes, with the average score increasing from 70.5 in Cycle I to 85.3 in Cycle II, and classical learning mastery reaching 90%. In addition, students’ learning activities and motivation also improved, as indicated by their enthusiasm during the learning process and positive responses to the interactive and competitive features of Quizizz. It can be concluded that the use of Quizizz as an interactive learning medium is effective in improving students’ learning outcomes, motivation, and engagement, and therefore can be used as an alternative innovative learning medium at SMK Negeri 4 Gowa